A photonic crystal laser from solution based organo-lead iodide perovskite thin films - Chen, Songtao (2020)
Perovskite semiconductors are actively investigated for high performance solar cells. Their large optical absorption coefficient and facile solution-based, low-temperature synthesis of thin films make perovskites also a candidate for light-emitting devices across the visible and near-infrared. Specific to their potential as optical gain medium for lasers, early work has demonstrated amplified spontaneous emission and lasing at attractively low thresholds of photoexcitation. Here, we take an important step toward practically usable perovskite lasers where a solution-processed thin film is embedded within a two-dimensional photonic crystal resonator. We demonstrate high degree of temporally and spatially coherent lasing whereby well-defined directional emission is achieved near 788 nm wavelength at optical pumping energy density threshold of 68.5 ± 3.0 μJ/cm(2). The measured power conversion efficiency and differential quantum efficiency of the perovskite photonic crystal laser are 13.8 ± 0.8% and 35.8 ± 5.4%, respectively. Importantly, our approach enables scalability of the thin film lasers to a two-dimensional multielement pixelated array of microlasers which we demonstrate as a proof-of-concept for possible projection display applications.